Biological and chemical changes in fluoroquinolone-associated tendinopathies: a systematic review. Issue 1 (27th February 2019) - Bisaccia, Domenico Rocco; Aicale, Rocco; Tarantino, Domiziano; Peretti, Giuseppe M; Maffulli, Nicola
Abstract: Introduction: The present systematic review investigates the biological and chemical mechanisms that affect the health and structure of tendons following the use of fluoroquinolones (FQs). Sources of data: A total of 12 articles were included, organized, and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Areas of agreement: Five mechanisms were identified: arrest of proliferation through a decreased activity of cyclin B, CDK-1, CHK-1, and increased PK-1; decrease tenocytes migration through decreased phosphorylation of FAK; decrease type I collagen metabolism through increased MMP-2; chelate effect on ions that influence epigenetics and several enzymes; fluoroquinolones-induced ROS (radical oxygen species) production in mitochondria. Areas of controversy: There is no definite structure-damage relationship. The dose–effect relationship is unclear. Growing points: Knowing and defining the damage exerted by FQs plays a role in clinical practice, replacing FQs with other antibacterial drugs or using antioxidants to attenuate their pathological effects. Areas timely for developing research: Clinical and basic sciences studies for each FQs are necessary.